Genetic parameters of yield component and yield in M1 rice (Oryza sativa L.) generation irradiated with gamma-ray - Riyanto, Agus; Oktaviani, Eka; Wulansari, Nur Kholida; Haryanto, Totok Agung Dwi (Universitas Padjadjaran, 2024)
High-yielding varieties are the primary determinant of the success of increasing Indonesia's rice production. Plant breeding for new high-yielding varieties is possible through mutation induction and selecting desired traits. The effectiveness and efficiency of selection require comprehensive genetic parameters. This study aimed to study the genetic diversity, heritability, genetic advance, and relationship between yield components and yield in the M1 generation of mutant rice irradiated with gamma ray. This research used a factorial randomized complete block design, involving gamma irradiation doses of 100 Gy, 150 Gy, and 200 Gy, as the first factor; and the second factor was the rice genotype: UnsoedBDBP, UnsoedBDIU, UnsoedBPIU, UnsoedIUBD, and UnsoedIBP. Each treatment was repeated three times. Results showed that traits with broad genetic variation were tiller number plant-1, grain number panicle-1, and grain yield plant-1. High heritability and genetic advance values were found in plant height, grain number panicle-1, and yield plant-1, indicating that improvement in these traits can be achieved simply through selection methods. Panicle number plant-1 and filled grain percentage panicle-1 showed a unidirectional relationship and directly affected high values on yield plant-1. Therefore, these traits can be considered selection indicators for breeding high-yielding mutant rice.